Toxicological Evaluation of the Complex Insectoacaricidal Preparation "Neoterika Protecto 12" - E. N. Indyuhova; M. V. Arisov; G. B. Arisova; I. A. Stepanova (Российский паразитологический журнал, 2019)
The purpose of the research: toxicological evaluation of a medicinal product for veterinary use "Neoterica Protecto 12" on laboratory animals. Materials and methods. White outbred rats, mice and guinea pigs were used in the experiment. In the study of acute oral toxicity in mice and rats, acute cutaneous toxicity, subacute toxicity, irritant action of an aqueous suspension of a combination of active substances, allergenic properties of the collar «Neoterika Protecto 12» conventional methods were used. Results and discussion. The median lethal doses LD50 for oral supplementation to white mice (1070 mg/kg) and oral supplementation to white rats (3210 mg/kg) were diagnosed, which allowed to designate the preparation to the 3rd hazard class (moderately hazardous substances). In the study of acute cutaneous toxicity on white rats LD50 amounted to more than 10 000 mg/kg, therefore, according to the generally accepted hygienic classification, the preparation belongs to the 4th hazard class during cutaneous application. In the study of subacute toxicity of the medication on rats for 6 months after application of the aqueous suspension of the combination of active ingredients in doses of 1000, 500 and 200 mg/kg, no changes in general state and behavior were observed in animals. When an aqueous suspension of a combination of active substances of the collar was applied to the skin of rats, there were no signs of irritant effect, but a mild effect on the mucous membrane of the guinea pig's eyes was recorded. It was found that the preparation does not have allergic and sensitizing effects.